The Implementation of MBKM at FKIP Muhammadiyah University Bengkulu - Yuniati, Ira; Onsardi, Onsardi; Ekowati, Sri; Finthariasari, Meilaty; Azhar, Andi; Perrodin, David D. (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The Minister of Education and Culture’s policy through Minister of Education and Culture Regulation Number 3 of 2020 concerning Higher Education Standards regarding Independent Learning on Independent Campuses (MBKM) seeks to give students the freedom to study in higher education as a form of learning innovation to obtain quality learning. The aim of the research is to find out how the existence of independent learning campus management education at the Faculty of Teacher Training and Education, Muhammadiyah University of Bengkulu, can be implemented well and what is the theory and practice in the learning process as seen from the four management functions, namely planning, organizing, implementing, and monitoring, which is usually abbreviated as POAC. This research is research with social and dynamic problems so that the researcher determines the use of descriptive qualitative research to search, collect, process, and analyze research data. The data sources in this research or those referred to as informants, are Deputy Dean 1 of FKIP UMB, Head of Study Program within FKIP, and students. Then non-human data sources include field notes, documents, and recorded interviews. Based on the results of the research and discussion, it is known that overall, it has gone quite well. However, from the evaluation results, there were still several problems encountered, especially regarding the conversion of grades from the MBKM program that students participated in. This is material for evaluation to improve in the future, especially in terms of the implementation of the MBKM Curriculum which is currently running.